Coparenting Approach to Being Successful Exclusively Breastfeeding - Maulida Nurfazriah Oktaviana; Fidawsyi Nuzula (Jurnal Kesehatan dr. Soebandi, 2024)
Breast milk is the first nutrient for infants because it contains essential nutrients for growth and development, so exclusive breastfeeding can prevent the risk of stunting and wasting in children. The lack of breastfeeding in infants is a threat to the long-term growth and development of children. Effective coparenting strongly impacts breastfeeding success rates because of its positive energy. Developing effective coparenting during the transition to becoming a parent is very helpful in the process of carrying out the role of parent, resolving conflict and supporting one's partner in raising children. The study aimed to analyze the success of Coparenting Approach to Being Successful Exclusively Breastfeeding. This research method is an observational study with an analytic cross-sectional design using a quantitative approach; the population in this study was 393 people in the Glagahagung Community Health Center Working Area sampling with a purposive sampling technique, based on inclusion and exclusion criteria where a number of respondents were exclusively breastfeeding with a total of 78 respondents. The results showed family support p value = 0.000, technological advances p value = 0.000, and lifestyle p value = 0.000. Based on the results show that the regression coefficient for family support is .716, this shows that increasing the family support variable will increase the coparenting approach variable in the success of providing EBF by .716, the trends and lifestyle regression coefficient is -.452, so this shows that trend and lifestyle variables reduce the influence on the coparenting approach in the success of providing EBF.